2021
DOI: 10.24042/ajipaud.v4i1.8334
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Kurikulum Merujuk KKNI Pada Prodi PIAUD

Abstract: Pengembangan IPTEKS yang sangat pesat menuntut pemerintah Indonesia melakukan review dalam segala bidang termasuk kurikulum pendidikan. Pemerintah Indonesia telah mencanangkan kurikulum merujuk Kerangka Kualifikasi Nasional Indonesia (KKNI) melalui Perpres No. 08 tahun 2012. Oleh karena itu, penelitian ini bertujuan untuk mengembangkan kurikulum merujuk KKNI pada program studi pendidikan islam anak usia dini (PIAUD) FITK UIN-SU Medan. Jenis penelitian ini merupakan penelitian dan pengembangan model Hannafin P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The results of this study provide evidence that teaching materials for rhythmic activity courses developed based on the IQF curriculum show that they are very well implemented in rhythmic activity learning. The results of previous relevant research conducted in the Early Childhood Islamic Education study program showed that the book product developed by referring to the IQF was very well used in learning (Wahyuni et al, 2021). Other studies have shown that the KKNI-oriented Acehnese cultural learning model is valid, practical, and effective, used (Tanjung, 2020), and in basic gymnastics learning the hybrid learning model (Sitepu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The results of this study provide evidence that teaching materials for rhythmic activity courses developed based on the IQF curriculum show that they are very well implemented in rhythmic activity learning. The results of previous relevant research conducted in the Early Childhood Islamic Education study program showed that the book product developed by referring to the IQF was very well used in learning (Wahyuni et al, 2021). Other studies have shown that the KKNI-oriented Acehnese cultural learning model is valid, practical, and effective, used (Tanjung, 2020), and in basic gymnastics learning the hybrid learning model (Sitepu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…The development of fundamental ideas like industry associations, professional associations, professional certification bodies or institutions, middle and high-level education and training institutions, and reliable and comprehensive accreditation bodies or institutions is what the Indonesian National Qualifications Framework, also known as the term, known by the abbreviation KKNI, is all about. The regulation that governs KKNI can be found in Presidential Regulation of the Republic of Indonesia Number 8 of 2012 (Wahyuni, Khadijah, Budianti, & Maisarah, 2021), in the context of the method of education and training, as a means of contributing to the formation of the character and identity of the Indonesian nation. The preparation of performance based on scientific elements, abilities, and expertise is the fundamental idea that underpins the KKNI's development (Rezeqi, Brata, Handayani, & Gani, 2020), this is in line with the learning outcomes that have been achieved through the education, training, or experience that has been completed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its inception through government regulations in 2012, numerous higher education institutions have adopted KKNI-based curricula. These curricula enhance the quality of teaching and learning processes, leading to improved outputs in terms of knowledge, skills, and attitudes (Wahyuni & Budianti, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The graduate should possess standard of ability that is in accordance with their respective levels. For example, undergraduate student must be able to achieve abilities at the 6th level, masters student achieve the 8th level, and doctorate student achieves the 9th level (Sutrisno, 2016;Wahyuni et al, 2021). These levels of educational attainment require universities to translate and describe them in real terms, especially in the learning process and learning outcomes to achieve.…”
Section: Introductionmentioning
confidence: 99%